UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR MELALUI LESSON STUDY - Samsuar Samsuar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by a conventional learning orientation where teacher-centered learning must be transformed into student-centered learning. The purpose of this study was to improve the professional competence of elementary school teachers through lesson study. This study uses a class action research design that has stages of planning, implementation, observation, and reflection. This research was conducted at the target schools in the city of Dumai. The research subjects were 10 V-grade teachers taken from each of the target schools. The research instrument used observation sheets and interview sheets. The results of this study indicate an increase in the professional competence of elementary school teachers through lesson study with the percentage of the first cycle of 64% with enough categories to 82% with good categories. The conclusion drawn is that the professional competence of teachers through Lesson Study has increased.